2023
DOI: 10.1002/lary.30540
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Laryngeal Sensory Function using a Tactile Aesthesiometer in Healthy Adults

Abstract: IntroductionLaryngeal sensory function in healthy adults was assessed through the delivery of tactile stimuli using Cheung–Bearelly monofilaments.Methods37 healthy adults were recruited with 340 tactile stimuli analyzed. Four calibrated tactile stimuli were delivered to three laryngeal sites: false vocal fold (FVF), aryepiglottic fold (AEF), and lateral pyriform sinus (LPS). Primary outcome was the elicitation of laryngeal adductor reflex (LAR). Secondary outcomes were gag, patient‐reported laryngeal sensation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 39 publications
5
11
0
Order By: Relevance
“…Ma et al investigated laryngeal sensory function using a tactile aesthesiometer in a cohort of 37 healthy adults and showed that for every 10 years of age increment, there was a 19% decrease in the odds of having a laryngeal adductor reflex. In their study, the tactile stimuli were delivered to the false vocal folds, aryepiglottic folds, and lateral pyriform sinus 13 . The negative correlation between smoking and tolerance reported in our study and in the study by Zheng et al is also substantiated by the exaggerated cough and excess of mucus noted in smokers.…”
Section: Discussionsupporting
confidence: 77%
“…Ma et al investigated laryngeal sensory function using a tactile aesthesiometer in a cohort of 37 healthy adults and showed that for every 10 years of age increment, there was a 19% decrease in the odds of having a laryngeal adductor reflex. In their study, the tactile stimuli were delivered to the false vocal folds, aryepiglottic folds, and lateral pyriform sinus 13 . The negative correlation between smoking and tolerance reported in our study and in the study by Zheng et al is also substantiated by the exaggerated cough and excess of mucus noted in smokers.…”
Section: Discussionsupporting
confidence: 77%
“…In a study by Halou et al, incubation of SWMs for at least 6 h in humid and hot environments reduced buckling force. 14 Although this study did not control for humidity and temperature, during sensory evaluation in the clinical setting, each aesthesiometer is used for an average of 11 min and 59 s. 15 These findings suggest that if distortion from salivary entrapment can be resolved and the aesthesiometer can be properly compressed, the delivered buckling force should not significantly change. In vivo clinical testing differs from the ex vivo in that the tissue mucosa will also be coated in saliva.…”
Section: Discussionmentioning
confidence: 91%
“…Tactile Force Measurement 4-0, 5-0, and 6-0 aesthesiometers were constructed, as detailed extensively in previous work, 7,10,15 fixing nylon suture to the end of an open-end ureteral catheter, leaving 30 mm exposed for compression 6 (Figure 2). An intermediate size, 4.5-0, was created using 5-0 nylon suture at a length of 25 mm.…”
Section: Stimulus Delivery Devicementioning
confidence: 99%
“…Healthy controls were defined as adults between 18 and 85 years of age without laryngopharyngeal disease and were subject to the same screening and exclusion criteria 23 . Additionally, controls were excluded if they had abnormal patient reported outcome measures (i.e., Reflux Symptom Index (RSI) score > 13, Eating Assessment Tool‐10 (EAT‐10) score > 2, or Voice Handicap Index‐10 (VHI‐10) score > 11).…”
Section: Methodsmentioning
confidence: 99%
“…The 6–0, 5–0, and 4–0 monofilaments deliver an increasing mean force of 0.03, 0.11, and 0.30 g respectively 12 . An intermediary strength “4.5–0” monofilament was created by using a 5–0 monofilament of 25 mm length, which has been demonstrated to have a mean buckling force of 0.19 g 23 …”
Section: Methodsmentioning
confidence: 99%